HEALTH SERVICE QUALITY VALUES OF PRIMARY CLINIC USING EPARTICIPATION SERVICE QUALITY ASSESSMENT - Siswanto, Joko; Lisangan, Erick Alfons; Zaenudin, Zaenudin (Informatika, Universitas Jenderal Soedirman, 2023)
The use of technology to manage participation in the quality of health services needs to be carried out to produce relevant, valid and accurate assessments of service quality. Not all Primary Clinics have health service quality standards and quality evaluation data for participation services using information technology (via electronic media). This is crucial for evaluating clinic development, upgrading the status to Main Clinic, and improving the service quality. The methodology used adopts the eParticipation framework with the stages of Areas of Participation (determining the main areas of participation), Category of Tools (determining the categories of ICT support tools), and Technology (determining ICT support technologies). The participation area is limited to Primary Clinic patients who act as participants of 1,308 people. 14 elements with a total of 33 detailed elements are the basic elements for assessing service quality. Application of eParticipation SQA website-based is used to manage and present the results of service quality assessments by Primary Clinic Managers. The highest average service quality assessment is in the answers to Good (62%), the Worse and Poor options are minimized, and the options of Good and Very Good are maximized. The technology required consists of software, hardware, and network devices. The application is supported by Manager and is used easily, quickly, and precisely.